2018
DOI: 10.1101/332098
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Higher rostral locus coeruleus integrity is associated with better memory performance in older adults

Abstract: For decades, the search for drivers of memory decline in human cognitive aging has focused on neocortical regions, the hippocampus, and dopaminergic neuromodulation. Recent findings indicate that the locus coeruleus (LC) and noradrenergic neuromodulation may also play an important role in shaping memory development in later life. However, technical challenges in non-invasive monitoring of LC integrity have hindered the study of LC-cognition associations in humans so far. Using high-resolution neuromelanin-sens… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 93 publications
3
10
2
Order By: Relevance
“…In the BASE-II dataset, there were no significant differences between young and older adults' overall LC-MRI contrast values (Bachman et al, 2021;Dahl et al, 2019). We also did not observe significant associations between LC-MRI contrast and diffusivity in either the LC or ascending noradrenergic bundle.…”
Section: Lc-mri Contrasts and Dticontrasting
confidence: 46%
“…In the BASE-II dataset, there were no significant differences between young and older adults' overall LC-MRI contrast values (Bachman et al, 2021;Dahl et al, 2019). We also did not observe significant associations between LC-MRI contrast and diffusivity in either the LC or ascending noradrenergic bundle.…”
Section: Lc-mri Contrasts and Dticontrasting
confidence: 46%
“…For the in vivo imaging of the LC, neuromelanin-sensitive MRI protocols were developed ( Keren et al, 2009 ; Priovoulos et al, 2018 ; Sasaki et al, 2006 ) and validated with histology ( Keren et al, 2015 ). These MRI protocols have been applied successfully in various studies to quantify the morphometry and signal intensity changes due to aging ( Betts et al, 2017 ; Clewett et al, 2015 ; Dahl et al, 2019 ; Liu et al, 2019 ) and AD ( Betts et al, 2019 ; Olivieri et al, 2019 ; Takahashi et al, 2015 ). In addition, resting state fMRI (rsfMRI) was applied recently to examine the functional connectivity of LC ( Jacobs et al, 2018b ; Zhang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The obtained LC signals are moderately consistent for scan-rescan reliability (Betts et al, 2017;Dahl et al, 2019;Langley et al, 2017;Tona et al, 2017) and achieve reliability indexes that are similar to those of bigger structures in less susceptible brain regions (Tona et al, 2017). Therefore, neuromelanin-sensitive MRI represents a promising, non-invasive method to determine structural alterations of the LC nucleus related to ageing or neurodegeneration.…”
Section: Figure 3 Neuromelanin-sensitive Mri Scansmentioning
confidence: 77%
“…Recently, neuromelanin-sensitive MRI was used to investigate the relationship between memory performance and LC integrity. Dahl et al (2019) reported that older participants showed better episodic memory when they had higher LC integrity.…”
Section: Figure 3 Neuromelanin-sensitive Mri Scansmentioning
confidence: 99%
See 1 more Smart Citation